Documentation of Sarawak Parang Model for Local Preservation - Muhyiddin, Mohammed; Auzani Zeda, Mohamed Kassim (International Journal of Multidisciplinary Research and Publications (IJMRAP), 2022)
The deployment of digitization technologies in the realm of culture and heritage is extensively established. Moreover, due to the wide range of current digitization technologies, determining the best solution for a specific problem is a huge difficulty. Other issues, how digital environment interaction links to physiological response of cultural. They suggest important scientific problems and inadequacies that must be solved in order for this shift to progress. To the best of our knowledge, no study on digitizing documentation of Sarawak Parang has been found in the literature. The aim of this research is to explore the viability of digital preservation for Sarawak Parang at the moment. The suggestions for Sarawak Parang further study can assist in developing and improve the traditional conservation of digital history and culture products and results. We were able to define parameters by applying modern digital documenting methods for this Sarawak Parang research. The findings of the study will add to significant information in the field of historical and creative management.